THE BRAVERY OF MILITARY BOMB SQUAD IN KATHRYN BIGELOW`S THE HURT LOCKER MOVIE (2009): A SOCIOLOGICAL APPROACH - YANUASTUTI, HIDAYAH (2011)
The major problem of this study is how bravery of military bomb squad is reflected in Kathryn Bigelow `s The Hurt Locker. The aim of this study is to analyze the movie based on the structural elements and to analyze the movie based on the sociological approach. This study belongs to qualitative method. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is The Hurt Locker movie itself, while the secondary data are taken from some information needed. The benefit of this study is to give additional information which can be used by other literature researchers who are interested in analyzing this play. Based on the analysis the writer draws the following conclusions as follow. First, the story of this play is based on true story during the Iraq war. So, there is relationship between the play and social reality. Second, after analyzing the structural elements of the movie, it can be concluded that all the structural elements, namely, Character and Characterization, casting, setting, plot, point of view, theme, mise en scene, sound, cinematography and editing have a unity. Third, the bravery of military bomb squad is the struggle between the life and death in The Hurt Locker.